5G multi-element/port antenna design for wireless applications:a review. Issue 9 (28th May 2019) - Gupta, Parul; Malviya, Leeladhar; Charhate, S. V.
Abstract: Fifth generation (5G) is the current hot topic of the world's leading telecommunication companies. The compact designs of antennas made it possible for them to resonate at higher frequencies, thus to enable the devices to attain higher data rate as compared to 4G technology. Data rate of 5G technology for low mobility users is expected to be 50.0 Gbps and for high mobility users it is 5.0 Gbps. On the other hand, International telecommunication union's objective for 5G is 3 times more spectrally efficient thanlong-term evolution (LTE). The paper has carried out meticulous study over the impact of 5G antennas on the size of antenna, size/type of substrate, gain, efficiency, and isolation, etc. Also, different arrays andmultiple input multiple outputs (MIMOs) with patch antenna, magneto electric-dipole, microstrip grid array antenna, folded dipole, series-fed array, connected antenna array, MIMO are studied. The paper also includes the existing technology i.e 4G LTE and their isolation enhancement approaches. Many of the designs used the reflector plates to reduce the back lobe radiation problem in MIMO/array antennas to increase front-to-back ratio. The gain in 5G antennas can be increased by using balun, parasitic element as directors, multiple notch structures, three identical slot sub-arrays, etc. Mathematical equations of multi-element/port antennas are included to model the designed antennas. The beam steering is also included for the 5G technology in this paper.